Corrosion behaviour of Ni-Cr alloys in wet CO2 atmosphere at 700 and 800 °C. (January 2019) - Xie, Yun; Nguyen, Thuan Dinh; Zhang, Jianqiang; Young, David J.
Highlights: Water vapour slowed the corrosion of alloys with 5–15 wt% Cr. Water vapour accelerated the thickening rate of chromia at 800 °C. Growth mechanism of chromia layer was changed in the presence of water vapour. The critical Cr content required for chromia maintenance was increased in wet CO2 . Abstract: The corrosion behaviour of binary Ni-Cr alloys with 5–30 wt% Cr was studied in Ar-20CO2 -20H2 O at 700 and 800 °C. Samples were electropolished before exposure to avoid the effect of surface cold work on alloy diffusion. At 700 °C, all alloys underwent both outer NiO formation and internal oxidation. At 800 °C, the alloys containing 5–20 wt% Cr developed non-protective scales, presenting high weight gain kinetics. However, the Ni-25Cr and Ni-30Cr alloys formed a continuous chromia layer, resulting in much reduced corrosion rates. The effects of water vapour on NiO growth, chromia formation and carburization are discussed.